Users' emotional experience using different modalities: a comparative study. (1st January 2014) - Chatzidaki, Eleni; Liapis, Alexandros; Tsironis, Alexandros; Xenos, Michalis; Kostaras, Nektarios
This paper describes a comparative study of users' emotional experience during their interaction with different input modalities. To this end, an experiment with three phases was conducted. In the first phase, the participants interacted with a personal computer via a keyboard and a mouse. The second phase involved their interaction with a tablet PC via a touch screen. Finally, in the third phase, the users interacted with the system using a wireless control through motion detection. Each phase of the experiment consisted of three scenarios relevant to the content. The evaluation methodology employed in this study was a combination of summative methods including questionnaires, interviews, observations and the recording of the users' actions (voice and video). The results of the comparative study indicated that the input modality of a system plays an important role in encouraging inexperienced users to interact with it.